Shaping urban ethics. The “making-of” a collective housing project at Berlin’s river Spree. - Ott, Max (Routledge, 2021)
Current discourses in the field of architecture are celebrating self-initiated collective housing as an outcome of joint efforts of altruistic people, who are committed to the idea of living in communities and, in contrast to the stake-holders of profit-oriented property developments, desire to actively contribute to the heterogeneity of their urban neighborhood. Against this background, this chapter discusses a cooperative project at Berlin’s river Spree as an example for an ethical project. However, it seeks to move beyond normative perspectives on collective housing as a “good” response to a “bad” real estate market, and therefore chooses two analytical approaches. On the one hand, it takes a closer look on the mutual relationship between ideals of cooperative cohabitation and their physical dimension and suggests an understanding of architecture as a process of social creativity that has a decisive role in shaping urban ethics. On the other hand, it argues that ethical claims to develop inclusive spatial structures do not express individual virtue but have to be considered as deeply interwoven with both needs and options of urban middle-class dwellers to justify their appropriation of scarce inner-city properties in the context of ongoing socio-spatial rearrangements.
Keywords: Gemeinschaftswohnen; Sozialbewegung; Kollektiv; Baugemeinschaft; Wohnprojekt; Ethik; Wertvorstellung; Wohnvorstellung; Lebensstil; Ideologie; Mittelschicht; Projektbericht